Addressing Food Insecurity in College: Mapping a Shared Conceptual Framework for Campus Pantries in Michigan. Issue 1 (24th July 2018) - Reppond, Harmony A.; Thomas‐Brown, Karen; Sampson, Natalie R.; Price, Carmel E.
Abstract: The first known university food pantry started at Michigan State University in 1993. Since then, campus food pantries are more widespread, although little is known about them. The current study examined how college pantries best serve students and foster their success. Twenty‐eight food pantry directors and staff from across sixteen Michigan college campuses engaged in concept mapping, a technique used to examine the interrelationships among concepts understood by stakeholders. Analyses identified six concepts, examined importance of each concept as assigned by participants, and evaluated variation among institutions. Implications for findings and future research directions are discussed.